2016
DOI: 10.7727/wimj.2016.328
|View full text |Cite
|
Sign up to set email alerts
|

Protective Mechanism of A20 Protein Overexpression in Acute Myocardial Infarction Rats

Abstract: Objective: To investigate the protective mechanism of zinc finger protein A20 over-expression in acute myocardial infarction (AMI) rats. Methods: Forty-five Sprague Dawley (SD) rats were randomly divided into sham group, model group and observation group. The model and observation groups were injected with normal saline and pcDNA3.1-A20 plasmid in the pre-operative 24 hour, respectively. The AMI model was established by ligating the left anterior descending coronary arteries of the model group and the observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…It has been reported that ginsenosides such as Rb1 (Zhu et al, 2022), Re (Li et al, 2013), Rg3 , Rg1 (Xu et al, 2019), Rb3 (Wu et al, 2022), and F2 and their metabolites can improve the level of lipid metabolism through antioxidation. Under physiological conditions, Nrf2 is anchored in the cytoplasm by Kelch-like epichlorohydrin-associated protein-1 (KEAP1) to prevent its translocation to the nucleus.…”
Section: Ginsenosides Enhance the Expression Of Antioxidant Enzymesmentioning
confidence: 99%
“…It has been reported that ginsenosides such as Rb1 (Zhu et al, 2022), Re (Li et al, 2013), Rg3 , Rg1 (Xu et al, 2019), Rb3 (Wu et al, 2022), and F2 and their metabolites can improve the level of lipid metabolism through antioxidation. Under physiological conditions, Nrf2 is anchored in the cytoplasm by Kelch-like epichlorohydrin-associated protein-1 (KEAP1) to prevent its translocation to the nucleus.…”
Section: Ginsenosides Enhance the Expression Of Antioxidant Enzymesmentioning
confidence: 99%